Prevalence of Chronic Polypharmacy in Community-Dwelling Elderly People in Poland: Analysis of National Real-World Database Helps to Identify High Risk Group - Kardas, Przemysław; Lichwierowicz, Aneta; Urbański, Filip; Chudzyńska, Ewa; Czech, Marcin; Kardas, Grzegorz (Frontiers in Pharmacology, 2021)
Introduction: Multimorbidity often comes with age, making elderly people particularly prone to polypharmacy. Polypharmacy, in turn, is a risk factor for adverse drug reactions, drug-drug interactions, non-adherence to medication, negative health outcomes, and increased healthcare services utilization. The longer the exposure to polypharmacy is, the higher the risk of these consequences is. Therefore, a detailed assessment of the prevalence and drivers of chronic polypharmacy in the elderly is particularly important. Aim of study: To find out the prevalence of chronic polypharmacy in the elderly population of Poland, and to characterize the subgroup with the highest risk of this problem, using real-world data. Methodology: A retrospective analysis of data on dispensation and healthcare services utilization held by the national payer organization for the year 2018. Chronic polypharmacy was defined as possession, as a result of dispensation, of five or more prescribed drugs within 80% of each of the consecutive six months. Results: Chronic polypharmacy was found in 554.1 thousand patients, i.e. in 19.1% of the national 65+ cohort. On average, those patients were 76 years old, and 49.3% of them were female. The vast majority (68.6%) continued their polypharmacy for the period of the whole year. There was a marked variation in geographical distribution of chronic polypharmacy with the highest value of 1.7 thousand per 100 000 inhabitants in the Łódź Voivodeship. Patients exposed to chronic polypharmacy filled prescriptions from 4.5 +/- 2.36 healthcare professionals. The average number of drugs they used was 8.3 +/- 3.84 DDD per patient per day. The most often prescribed drugs were Metformin, Atorvastatin and Pantoprazole. The average annual hospitalisation rate in those patients was 1.03 +/- 2.4. Conclusion: This study was the first of this kind involving a nationwide assessment of chronic polypharmacy in Polish elderly. We found that this problem affected one fifth of Polish older adults and it remains stable due to its direct relation to chronic conditions. Thus, our results confirm that this phenomenon is highly important for the national health policy and requires relevant interventions. The planned introduction of pharmaceutical care in Poland is expected to help in solving the problem.